2012
DOI: 10.1007/s00467-012-2369-4
|View full text |Cite
|
Sign up to set email alerts
|

Fluid overload and mortality are associated with acute kidney injury in sick near-term/term neonate

Abstract: Background Acute kidney injury (AKI) is common and portends mortality in several neonatal cohorts. Fluid overload is independently associated with poor outcomes in children and adults but has not been extensively studied in neonates. Methods Between February 2010 and May 2011, we followed 58 neonates who met the following criteria: birth weight >2,000 g, gestational age ≥34 weeks, 5-min Apgar ≤7, and parental consent. Serum creatinine (SCr) was measured daily for first 4 days of life. AKI was defined as a ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
80
1
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 25 publications
(22 reference statements)
7
80
1
6
Order By: Relevance
“…89 Limited data are available on fluid overload in neonates. Askenazi et al 63 showed that sick late preterm neonates with AKI had a higher median fluid overload at day of life 3 than those without AKI (+8.2% vs -4%, P , .001). As fluid overload is a potentially modifiable risk factor for mortality, research into its impact on neonatal outcomes is critical to provide information to clinicians about fluid provision and the timing of renal replacement therapy.…”
Section: Neonatal Cardiac Surgerymentioning
confidence: 99%
“…89 Limited data are available on fluid overload in neonates. Askenazi et al 63 showed that sick late preterm neonates with AKI had a higher median fluid overload at day of life 3 than those without AKI (+8.2% vs -4%, P , .001). As fluid overload is a potentially modifiable risk factor for mortality, research into its impact on neonatal outcomes is critical to provide information to clinicians about fluid provision and the timing of renal replacement therapy.…”
Section: Neonatal Cardiac Surgerymentioning
confidence: 99%
“…A cohort study reported that 67% severe sepsis patients developed evidence of fluid overload in first day under EGDT, which was associated with high risk of mortality [7]. Furthermore, compared with non-AKI patients, ample recent data have reported that higher rate of fluid overload was found in AKI patients, and fluid overload is associated with increased mortality rate in AKI patients [8][9][10]. There are also several studies reporting the association between fluid overload and kidney recovery, but results are still controversial [11,12].…”
Section: Introductionmentioning
confidence: 97%
“…Tissue edema may directly participate in the progression of AKI [8,9,15,19,24]. The previous studies conducted in children and infants suggest that both AKI and FO were associated with increased mortality [3,28]. However, whether or not the association of FO with mortality is due to direct effects of FO itself or due to indirect associations between FO and other disease states, such as AKI, is unknown [9].…”
Section: Introductionmentioning
confidence: 99%